PROFESSIONAL SOCIALIZATION OF THE SPORT COACH AS A FORMATIVE PROCESS OF KNOWLEDGE ACQUIRING - Rodrigues, Heitor de Andrade; Paes, Roberto Rodrigues; Souza Neto, Samuel de [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2016)
The purpose of the research was to investigate the process of professional socialization of youth basketball coaches, in order to identify the knowledge acquired throughout time and analyze the nature of the formation processes behind the appropriation of knowledge. It was chosen a quantitative research, with the narrative interview, ethno-sociological perspective, to collect technical data. Thirteen coaches were chosen for the research. The results revealed the appropriation of a diverse set of knowledge (experiential, academic and professional), the product of successive socialization, supported by artisanal education, academic-scientific background and reflective practice.
Keywords: Socialization; Knowledge; Coaches